The Impact of Language Loss on the Māori Performing Arts - Ka'ai-Mahuta, Rachael (Te Kaharoa, 2008)
This article explores the close relationship between the loss of Te Reo Maori and the impact on Maori performing arts. The crucial role of language as the central component to Maori performing arts is examined, and the revival of Te reo Maori is considered as a parallel development to the growth in the number of Te Reo speakers since the 1970s.